Discriminación arancelaria y decisiones de localización de las empresas - Mendez, Jose (Estudios de Economía, 2016)
The purpose of this paper is to analyse the effects of economic integration among countries on firms investment decisions when such decisions are taken strategically. It is shown that, in this context, the traditional “tariff jumping” argument is not always applicable and that localisation decisions depend on the existing relationship between tariff discrimination and market size. It is argued that economic integration disincentives national firms market entry.